2014
DOI: 10.1002/2014jd022367
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the channel‐bottom light intensity and channel‐base current of a rocket‐triggered lightning flash

Abstract: The correlations between channel-bottom light intensity and channel-base current of all discharge processes of a rocket-and-wire-triggered lightning flash, including initial continuous current (ICC) pulses, ICC pulse background continuing current (IBCC), return strokes, M components, and M component background continuing currents (MBCC), have been investigated. A rough linear correlation has been found between the current squared and the light intensity for ICC pulses (including peaks of different ICC pulses),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…In Figure , ℓ R also appears to fit a quadratic in I p slightly better than ℓ o fits a quadratic, and similar trends been reported by Zhou et al . [] during the “initial rising stage” of a RS, i.e., during the fast rise to peak (for many of the same events) and by Carvalho et al . [] for the bottom of the channel in RTL.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure , ℓ R also appears to fit a quadratic in I p slightly better than ℓ o fits a quadratic, and similar trends been reported by Zhou et al . [] during the “initial rising stage” of a RS, i.e., during the fast rise to peak (for many of the same events) and by Carvalho et al . [] for the bottom of the channel in RTL.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [] reported that M‐component and initial continuous current (ICC) pulses in triggered lightning having risetimes in the range of 10 µs to 100 µs for both current and luminosity at the ground exhibited a current‐to‐luminosity delay on the order of the current and luminosity risetimes. Thus, from Carvalho et al [] and Zhou et al [], it would appear that the observed delay between current and luminosity at the ground increases with both increasing current risetime and increasing luminosity risetime.…”
Section: Introductionmentioning
confidence: 99%
“…And also the longer the channel segment viewed by the sensor, the wider the light waveform it detected. These results can well explain those observed light waveforms of return strokes in literature [ Wang et al ., ; Zhou et al ., ].…”
Section: Modeling Resultsmentioning
confidence: 99%
“…[] and Zhou et al . [] compared the current and optical signal with a high speed detection system for triggered lightning discharges. They found that the rising front of the current is always faster than that of the optical signal, which are well consistent with our simulation results.…”
Section: Modeling Resultsmentioning
confidence: 99%